Pengaruh Pelatihan, Pengembangan Karir, dan Kompensasi Terhadap Kinerja Pegawai Pada PT. PLN (Persero) Unit Induk Distribusi Jawa Barat - Mario Xaverius Wahyu Catur Prasetyo; Muhamad Arief Noor; Joned Ceilendra Saksana (Cakrawala : Jurnal Penelitian Mahasiswa, 2026)
The purpose of this study is to find out and analyze the influence of human resource management practices consist of human resource training, career development and compensation for employee performance at PT PLN (persero) Unit Induk Distribusi Jawa Barat. The object of study was PT PLN (Persero) Unit Induk Distribusi Jawa Barat. This research is a quantitative research with respondents namely employees of PT PLN (Persero) Unit Induk Distribusi Jawa Barat, for the population of the study that is as many as 49 people and the sample of the study is 40 people.         Research method used are descriptive analysis models and multiple linear regression models. The results of the study show that order to optimize employee performance, the company should provide motivation or direction from superiors to employees in participating in the training. The company is also expected to conduct regular evaluations of employees after training.